(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Introduction: The pandemic COVID-19 not only caused grievous public health problems but also caused enormous psychological distress, especially among the medical support staff. These mental health issues leading to Generalized Anxiety Disorder (GAD). Ther is a lack of substantial data on psychological effects due to COVID pandemic on Bangladeshi medical health workers. This study aims to provide prevalence of GAD on Bangladeshi health workers Objective: The study aimed to investigate the prevalence of generalized anxiety disorder among medical support staff (Doctors & Health Care Workers) in some hospitals during the COVID-19 pandemic swept over Bangladesh recruited from Dhaka division. Face-to-face interviews were conducted to obtain Socio-demographic data using a semi structured to learn status of the COVID-19 pandemic in those hospitals and anxiety symptoms among those Docs/HCWS. Result: In this study of total 289 study populations majority (65.7%) were male and (34.3%) were female. With a mean age of 31.09±8.91 years. Majority of them (64.4%) used to work indoor, while 11.1% worked outdoors, 8.0% in emergency department and 16.6% in critical care unit (OT, ICU and HDU). Out of all those Docs/HCWS 51.2% use to be in direct contact with COVID-19 suspected patients feverish or infected, 48.8% did not. More than half of those Docs/HCWS participated less self-protection against COVID-19 of the (55.4%) Docs/HCWS had a little trust in infection control measures practised by the health care authority and just over half (52.2%) were worried on being infected with COVID-19. Among them, 73.4% lived with their family. Nearly 2/3rd of the participants or persons they were living with (64.7%), didn’t get infected by COVID-19. Among those who looked for COVID-19-related information, 59.6% spent at least 30 minutes daily. The majority of the respondents (58.0%) had minimal anxiety and others had variable levels of generalized anxiety disorder. Conclusion: Measures should be taken to overcome the obstacles to improve the betterment of the working status and service. The Journal of Ad-din Women’s Medical College; Vol. 11 (2), July 2023; p 26-31